Screening of Hydrocarbon-Stapled Peptides for Inhibition of Calcium-Triggered Exocytosis - Lai, Ying; Tuvim, Michael J.; Leitz, Jeremy; Peters, John; Pfuetzner, Richard A.; Esquivies, Luis; Zhou, Qiangjun; Czako, Barbara; Cross, Jason B.; Jones, Philip; Dickey, Burton F.; Brunger, Axel T. (Frontiers in Pharmacology, 2022)
The so-called primary interface between the SNARE complex and synaptotagmin-1 (Syt1) is essential for Ca2+-triggered neurotransmitter release in neuronal synapses. The interacting residues of the primary interface are conserved across different species for synaptotagmins (Syt1, Syt2, Syt9), SNAP-25, and syntaxin-1A homologs involved in fast synchronous release. This Ca2+-independent interface forms prior to Ca2+-triggering and plays a role in synaptic vesicle priming. This primary interface is also conserved in the fusion machinery that is responsible for mucin granule membrane fusion. Ca2+ stimulated mucin secretion is mediated by the SNAREs syntaxin-3, SNAP-23, VAMP8, synaptotagmin-2, and other proteins. Here, we designed and screened a series of hydrocarbon-stapled peptides consisting of SNAP-25 fragments that included some of the key residues involved in the primary interface as observed in high-resolution crystal structures. We selected a subset of four stapled peptides that were highly α-helical as assessed by circular dichroism and that inhibited both Ca2+-independent and Ca2+-triggered ensemble lipid-mixing with neuronal SNAREs and Syt1. In a single-vesicle content-mixing assay with reconstituted neuronal SNAREs and synaptotagmin-1 or with reconstituted airway SNAREs and synaptotagmin-2, the selected peptides also suppressed Ca2+-triggered fusion. Taken together, hydrocarbon-stapled peptides that interfere with the primary interface consequently inhibit Ca2+-triggered exocytosis. Our inhibitor screen suggests that these compounds may be useful to combat mucus hypersecretion that is a major cause of airway obstruction in the pathophysiology of asthma and cystic fibrosis.